التمويل التكافلي لنفقات الحج مقترح نموذج للتطبيق - الفارسي, مفتاح إبراهيم مفتاح (Scientific Journal of University of Benghazi, 2021)
This study aims to determine the possibility of financing the expenses of Hajj Takafula through studying the concept of Hajj and the concept of ability, as well as the funding of Takaful and the legitimacy of the expenses of Hajj by answering the main question of this study which is: Is it possible for Hajj expenses can be funded by Takaful? The researcher followed the inductive and deductive method by examining the literature related to this study from books and scientific magazines, forming a financing model and testing it on the Libyan society, and indicating the elements of its implementation. The study gets a number of results, the most important which is that the financial ability and the means of access to it can be in many ways, such as the Possession, and the interdependence among the society. This financing model is depended on the concept of Takaful which is based on the donation contracts, which through it all Muslims who wish to perform this one of the pillars of Islam can progress In order to obtain an opportunity for a fair choice due to the Organization of Islamic Cooperation Resolution No. 17/21-C concerning the determination of the numbers of expatriate Muslims to perform Hajj.